Seleção divergente do gene LWS entre ciclídeos neotropicais e africanos. - Fabrin, Thomaz Mansini Carrenho (2019)
Cichlidae presents great ecomorphological diversification, in both African lakes and Neotropical regions. Because these organisms use the vision for feeding, sexual selection, as well influencing other behavioural characteristics, it is important obtaining molecular data about the evolution of the genes which expresses visual pigments. Among these genes, the long-wavelength sensitive (LWS) gene it is important for evolutionary studies, because your great variation. So was observed the codons under selection using partial fragments of the codifying sequence of the LWS gene, comparing Neotropical and African cichlids, besides estimate the rate variation of this gene in Neotropical group and correlate this to the variation of the mitochondrial gene COI. Partial fragments of the genes LWS and COI of the Neotropical cichlids were sequenced, and sequences of the African species were obtained from GenBank. It was possible to detect the divergent selection between them, Neotropical and African cichlids, besides different rate variation of the LWS gene among different Neotropical clade, considering previous temporal divergence. The results obtained contribute to the understand of the molecular evolution in the visual system of the Neotropical cichlids, once key-sites of the LWS protein are under selection in this group, and possibly ecomorphological characteristic imply the rate variation of the LWS gene.